Konvergensi Pendapatan Regional Kota dan Kabupaten di Indonesia - Haryo Kuncoro (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
This paper aims to explore regional dynamics of real per capita income among municipalities in the case of Indonesia over the period of 1988-2003. First, the behavior of dynamics of real per capita income over time is analyzed by visual inspection of their distributions using Theil index and spatial statistics. Next, we employ the traditional approach to predict a pattern of convergence among municipalities. Our tentative conclusions that can be drawn from the two analyses are as follows. First, there is a high level of persistence in the relative position of municipalities, consistent with a low degree of mobility in the income distribution. Second, the richest municipalities tend to polarize gradually, which may be attributed to externalities linked to localization or to the proximity the surrounding areas. Third, private investment and de-concentration fund positively support to the convergence mechanism. Those findings suggest that spatial interdependency seems to have fostered growth of per capita income in those municipalities. Key words: Convergence, Intergovernmental Transfer, Moran’I Statistics, Theil Index